Handbook of mobile learning - Berge, Zane L.; Muilenburg, Lin Y.; Crompton, Helen (Routledge, 2013)
Winner of the AECT Division of Distance Learning (DDL) Distance Education Book Award! This handbook provides a comprehensive compendium of research in all aspects of mobile learning, one of the most significant ongoing global developments in the entire field of education. Rather than focus on specific technologies, expert authors discuss how best to utilize technology in the service of improving teaching and learning. For more than a decade, researchers and practitioners have been exploring this area of study as the growing popularity of smartphones, tablets, and other such devices, as well as the increasingly sophisticated applications for these devices, has allowed educators to accommodate and support an increasingly mobile society. This handbook provides the first authoritative account of the theory and research that underlies mobile learning, while also exemplifying models of current and future practice.